Towards relevant theological education in Africa: comparing the international discourse with contextual challenges - W. P. Wahl (Acta Theologica)
During the past five decades the heartland of global Christianity has shifted to the Southern hemisphere. This places the responsibility of future Christianity predominantly in the hands of church leaders in these regions. It is therefore crucial to critically reflect on how effective theological education is to produce competent church leaders, especially in Africa. This article aims to give an overview of the challenges theological education in Africa is currently facing, and then to provide a macro vision of the major moments in the development of the international discourse on theological education over the past five decades. This comparison will inform practitioners about the relevance of current models used for theological education in Africa. By highlighting the relevance of these various models and how they relate to challenges in Africa, this article contributes to research on the development of new and alternative frameworks for theological education in an African context.